Ghana's experiments with business-government co-ordination - Ernest Aryeetey; Nkechi Owoo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The article explores the various co-ordination mechanisms between the state and the business community in Ghana, and the implications for economic growth in the country. We focus on three periods in the economic history of state-business relations: the immediate post-independence period and the adoption of a statist approach to development where the state was the main engine for development; the period of military rule that was characterized by some semblance of civility in the relations between the state and the private sector; and the post-military regime, where positive relationships with the private sector were deliberately developed and cultivated.
Keywords: L00; N1; H11; P16; 330; state-business relations; private sector; economic growth; Ghana